The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1002/ajmg.a.31353
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive genetic analysis of relevant four genes in 49 patients with Marfan syndrome or Marfan‐related phenotypes

Abstract: In order to evaluate the contribution of FBN1, FBN2, TGFBR1, and TGFBR2 mutations to the Marfan syndrome (MFS) phenotype, the four genes were analyzed by direct sequencing in 49 patients with MFS or suspected MFS as a cohort study. A total of 27 FBN1 mutations (22 novel) in 27 patients (55%, 27/49), 1 novel TGFBR1 mutation in 1 (2%, 1/49), and 2 recurrent TGFBR2 mutations in 2 (4%, 2/49) were identified. No FBN2 mutation was found. Three patients with either TGFBR1 or TGFBR2 abnormality did not fulfill the Ghe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 24 publications
3
42
0
4
Order By: Relevance
“…(Singh et al 2006). However, it should be noted that arterial tortuosity, a cardinal feature of LDS, was not systematically evaluated in any of the four studies (Disabella et al 2006;Matyas et al 2006;Sakai et al 2006;Singh et al 2006). Moreover, two research groups were unable to identify TGFBR2 mutations in 29 MFS patients (FBN1 was normal in 24 and unknown in five) (Ki et al 2005) and seven patients (FBN1 was normal) with MFS compatible with the Ghent criteria (Loeys et al 2005).…”
Section: Germline Tgfbr Mutations and Connective Tissue Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…(Singh et al 2006). However, it should be noted that arterial tortuosity, a cardinal feature of LDS, was not systematically evaluated in any of the four studies (Disabella et al 2006;Matyas et al 2006;Sakai et al 2006;Singh et al 2006). Moreover, two research groups were unable to identify TGFBR2 mutations in 29 MFS patients (FBN1 was normal in 24 and unknown in five) (Ki et al 2005) and seven patients (FBN1 was normal) with MFS compatible with the Ghent criteria (Loeys et al 2005).…”
Section: Germline Tgfbr Mutations and Connective Tissue Disordersmentioning
confidence: 99%
“…At least six TGFBR2 mutations (R356P, N384S, R460H, R460C, S449F, and R537C) and two TGFBR1 mutations (S241L and R487Q) were recognized in two or three conditions (i.e., R460H found in MFS, LDS, and TAAD) (Ades et al 2006;Disabella et al 2006;Ki et al 2005;Loeys et al 2006;Matyas et al 2006;Mizuguchi et al 2004;Pannu et al 2005a;Sakai et al 2006;Singh et al 2006) (Fig. 1, Table 2), implying that TGFBR mutations may cause various clinical consequences or that appropriate diagnosis is rather difficult for these disorders.…”
Section: Germline Tgfbr Mutations and Connective Tissue Disordersmentioning
confidence: 99%
“…11,16 In our study, although 10 patients with the TGFBR mutations had phenotypic variability, genetic analysis can be used to differentiate LDS from Marfan syndrome or from familial thoracic aortic aneurysm and dissection. Prior studies have suggested that some TGFBR2 mutations are present in families whose members have not only LDS (p.Arg495X), 2 but also classic Marfan syndrome (p.Ser449Phe), 5 or incomplete Marfan syndrome (p.Trp504X) 6 and TGFBR1 mutations are present in patients with familial thoracic aortic aneurysm and dissection (p.Arg487Gln).…”
Section: Genetic Analysismentioning
confidence: 79%
“…3,8 To our knowledge, in previous studies of Oriental populations, patients with LDS type II were not identified. [9][10][11][12][13] Accordingly, a large-scale clinical study is needed to identify whether differences in the frequencies of LDS type I and II can be attributed to racial differences.…”
Section: Clinical Findingsmentioning
confidence: 99%
“…This study identified FBN1 mutations in 91% of MFS patients (Loeys et al 2004). A study of direct DNA sequencing of the exons and flanking introns of FBN1, FBN2, TGFBR1, and TGFBR2 on 49 MFS or MFS-suspected patients identified FBN1 mutations in 55% of patients and TGFBR1 and TGFBR2 mutations in 6% of patients [Sakai et al 2006]. The MFS patients in these studies in whom no mutations were detected could have cryptic FBN1 mutations or locus heterogeneity for MFS (Boileau et al 1993).…”
Section: Discussionmentioning
confidence: 85%